Analisis Ideologi Patriarki dan Upaya Pembungkaman atas Gerakan Politik Perempuan dalam Novel John Steinbuck: â€œOf Mice and Menâ€ dan â€œTortilla Flatâ€ - Chusnul Chotimmah; Koko Srimulyo; Ervan Kus Indarto (Universitas Batanghari Jambi, 2023)
This study aims to analyze efforts to silence women's political movements in the 1930s through narratives perpetuating patriarchal ideology in two novels by John Steinbeck: Tortilla Flat and Of Mice and Men. This research is a literature study using a descriptive qualitative analysis approach in order to present a more varied perspective in viewing John Steinbeck's contribution to American politics. Two of Steinbeck's novels are examined as material to analyze attempts to silence women's political movements in their time by using theories from feminist critics, such as Judith Butler and See Gayle Rubin. The results of this study found that there is weakening of roles, strengthening stereotypes, and giving stigma to female characters in Steinbeck's stories which are considered as an effort to build narratives that marginalized women, as well as repetition of discourse to strengthen patriarchal ideology in Steinbeck's texts.